A contribuição do programa residência pedagógica na formação inicial de professores que ensinarão matemática - PEREIRA, Graziela Vilaça (2024)
This text aims to describe the experience report of the activities of the Pedagogical Residency Program, of the Mathematics Degree course of the Federal University of Pará (UFPA) in the municipality of Abaetetuba. The aim of this work is to address and describe the practices adopted and methodologies used by the residents of the Prof. Benvinda de Araújo Pontes State School of Elementary and Secondary Education in the 2nd grade of High School. In this sense, the construction of experiences that make it possible to expand the theoretical and practical knowledge of the residents is highlighted, which is fundamental for professional improvement and teacher training. Thus, we aim to understand the initial training of the residents of the Pedagogical Residency Program (PRP) who will teach mathematics, based on the objectives related to the program.